2006
DOI: 10.1152/ajpheart.01137.2005
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin-induced cardioprotection is mediated by increasing inducible nitric oxide synthase and consequent S-nitrosylation of cyclooxygenase-2

Abstract: We determined the effects of cyclooxygenase-1 (COX-1; SC-560), COX-2 (SC-58125), and inducible nitric oxide synthase (iNOS; 1400W) inhibitors on atorvastatin (ATV)-induced myocardial protection and whether iNOS mediates the ATV-induced increases in COX-2. Sprague-Dawley rats received 10 mg ATV.kg(-1).day(-1) added to drinking water or water alone for 3 days and received intravenous SC-58125, SC-560, 1400W, or vehicle alone. Anesthesia was induced with ketamine and xylazine and maintained with isoflurane. Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
142
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 56 publications
5
142
1
4
Order By: Relevance
“…Subcutaneous 0.1 mg/kg buprenorphine was administered, the chest was closed, and the mice were recovered from anesthesia. Four hours after reperfusion, the mice were reanesthetized, the coronary artery was reoccluded, Evans blue dye (3%) was injected into the right ventricle, and the mice were euthanized under deep anesthesia (2,7,54,69).…”
Section: Infarct Sizementioning
confidence: 99%
See 3 more Smart Citations
“…Subcutaneous 0.1 mg/kg buprenorphine was administered, the chest was closed, and the mice were recovered from anesthesia. Four hours after reperfusion, the mice were reanesthetized, the coronary artery was reoccluded, Evans blue dye (3%) was injected into the right ventricle, and the mice were euthanized under deep anesthesia (2,7,54,69).…”
Section: Infarct Sizementioning
confidence: 99%
“…Scalia et al (49) has shown that simvastatin does not limit IS in iNOS Ϫ/Ϫ mice. Our laboratory showed that 1400W, a specific iNOS inhibitor, abrogated the IS-limiting effects of atorvastatin in the rat without affecting eNOS (2) and, more recently, that atorvastatin failed to decrease IS in iNOS Ϫ/Ϫ mice (71). The cardioprotection by preconditioning diminishes with age (17,20,30), hypertension (17,20), diabetes (20), and atherosclerosis (20).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Perhaps, the most likely mechanism by which statins provide protection against ischaemia and reperfusion-induced arrhythmias is their ability to increase NO synthesis (Mital et al, 2000;Lefer et al, 2001;Atar et al 2006). We have substantial previous evidence that NO plays an essential role in both the early and delayed anti-arrhythmic effects of preconditioning, induced either by brief periods of coronary artery occlusion (Végh et al, 1992b), cardiac pacing (Kis et al, 1999) or heavy physical exercise (Babai et al, 2002).…”
Section: Introductionmentioning
confidence: 91%